2023
DOI: 10.1021/acs.jpca.3c01174
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Structures and Spectroscopic Parameters of Phenylalanine and Tyrosine in the Gas Phase: A Joint Venture of DFT and Composite Wave-Function Methods

Abstract: A general strategy for the accurate computation of conformational and spectroscopic properties of flexible molecules in the gas phase is applied to two representative proteinogenic amino acids with aromatic side chains, namely, phenylalanine and tyrosine. The main features of all the most stable conformers predicted by this computational strategy closely match those of the species detected in microwave and infrared experiments. Together with their intrinsic interest, the accuracy of the results obtained with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 100 publications
1
13
0
Order By: Relevance
“…This procedure has been validated for several amino acids containing polar or aromatic side chains. , However, the presence of topological changes (i.e., different bonding patterns) in the different tautomers might require QC methods even more accurate than those validated for the analysis of conformer stabilities. Here this problem is tackled for the particularly challenging case of cytosine in the gas phase, with special reference to the MW and IR spectra of the different tautomers.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has been validated for several amino acids containing polar or aromatic side chains. , However, the presence of topological changes (i.e., different bonding patterns) in the different tautomers might require QC methods even more accurate than those validated for the analysis of conformer stabilities. Here this problem is tackled for the particularly challenging case of cytosine in the gas phase, with special reference to the MW and IR spectra of the different tautomers.…”
Section: Introductionmentioning
confidence: 99%
“…An unbiased analysis of the role played by the different contributions on the overall experimental outcome calls for a preliminary investigation of gas phase processes. We have recently devised and validated a general computational strategy able to disentangle the complex conformational landscapes of amino acids. , Here, we tackle the problem of tautomeric equilibria, which involve bond pattern changes and are, therefore, more challenging for quantum chemical (QC) computations.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Amino acids represent a challenging playground for the validation of this approach since systematic investigations have revealed that the natural amino acids containing non-polar side chains present two dominant conformers (usually referred to as type I and type II), stabilized by intra-backbone hydrogen bonds. 7,[25][26][27] On the other hand, a,adialkylated a-amino acids show additional conformers due to the increase of energy barriers governing their relaxation to more stable counterparts. 28,29 In the context of chemical biology, a,a-dialkylated residues play a significant role since they are able to restrict the conformational freedom of peptide backbones.…”
Section: Introductionmentioning
confidence: 99%